On-going transmission of human onchocerciasis in the Massangam health district in the West Region of Cameroon: Better understanding transmission dynamics to inform changes in programmatic interventions - Bakajika, Didier; Senyonjo, Laura; Enyong, Peter; Oye, Joseph; Biholong, Benjamin; Elhassan, Elizabeth; Boakye, Daniel; Dixon, Ruth; Schmidt, Elena (PLOS Neglected Tropical Diseases, 2018)
Author summary The global goal is to eliminate onchocerciasis by 2025. However, not all areas are on track to do so, as is the case for Massangam health district (HD) in the West Region of Cameroon. A new strategy is required in order to accelerate efforts to reach elimination targets. This study aimed to better understand the transmission dynamics of Onchocerca volvulus in Massangam HD through the identification of black fly (Simulium damnosum) breeding sites, parasitological and entomological studies. The study was able to define an approximate 12 km area of high transmission encompassing four communities with very high levels of infection and evidence of on-going transmission in humans. This area is facilitated by perennial productive black fly breeding sites in the neighbouring rivers of the Nja and Mbam. Multi-faceted interventions are required to target the reservoir of infection facilitating transmission. We suggest the need for a new test and treat strategy in the area of high transmission (with a drug that kills the adult O. volvulus worm living in humans) and larviciding of the breeding sites of the black fly. In areas surrounding the area, increase distribution of ivermectin from annual to twice yearly distribution, whilst also using innovative strategies to improve compliance.